Valorization of Residues from Energy Conversion of Biomass for Advanced and Sustainable Material Applications - Enke, Dirk; Beidaghy Dizaji, Hossein; Lenz, Volker; Zeng, Thomas (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The focus of this Special Issue was on biomass ash valorization with respect to their potential for various material applications. Most of the publications in this Special Issue focused on the production of biogenic silica with different properties. Additionally, some of the publications considered application of biomass ashes and biochar as a fertilizer, for soil amendment and recovery of ash forming elements such as N and P, as well as the application of biomass feedstocks in biofuel production.Accordingly, ashes produced from the thermochemical conversion of agricultural residues have high potential to be utilized for different material applications. However, local availability, as well as scaling up the process and life-cycle assessment should be considered prior to the utilization of these materials. Furthermore, densification as a mechanical pre-treatment can be crucial to improve the fuel properties, while purification of some of the ash forming elements, such as calcium, potassium, and prosperous should also not be disregarded in future investigations.